Makna jilbab bagi perempuan Muslim Amerika: dinamika perjumpaan Islam dan budaya Amerika - M. Thoyibi (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
This study deals with how American Muslim women gave meanings to hijab. The data used consistedof the verbal expressions of the subject of the study. The data source included the documents of newsand talks conducted by the National Public Radio (NPR) headquartered at Washington D.C. The data-collecting method was library research. The study concluded that the various views on hijab amongAmerican Muslim were more than the diversity of interpretations of the scriptures. They representedthe encountering dynamics of Islam and American culture. At the economic domain, American cultureaccommodated the hijab as it may represent certain values that helped sell American products. At thesocial, political, and religious domains, however, Americans had a greater prejudice and resistance as theyassociated hijab with fundamentalism, fanaticism, extremism, and even terrorism.